The Impact Of Profitability And Liquidity On The Capital Structure - Safira Ainu Nadira Sofyan; Nurman; Rezky Amalia Hamka; Anwar Ramli; Annisa Paramaswary Aslam (Journal of Studies in Academic, Humanities, Research, and Innovation, 2025)
The real estate sector, as one of the most capital-intensive industries in Indonesia, experienced substantial financial fluctuation during the 2020–2024 period due to the economic impacts of the COVID-19 pandemic and subsequent monetary adjustments. These conditions raised important questions regarding the determinants of firms’ capital structure decisions, particularly profitability and liquidity. This study aims to examine the effect of profitability measured by return on assets (ROA) and liquidity measured by the current ratio (CR) on the capital structure of real estate companies listed on the Indonesia Stock Exchange. Using a quantitative associative design, the research analyzed 70 observations from 14 purposively selected companies with complete and consistent financial disclosures. Multiple linear regression was applied to assess both partial and simultaneous influences of the independent variables on the debt-to-equity ratio (DER). The results indicate that profitability has no significant effect on capital structure, suggesting that ROA does not play a central role in firms’ financing choices within this sector. In contrast, liquidity shows a negative and significant influence on DER, demonstrating that firms with stronger short-term financial capacity tend to reduce their reliance on debt financing. Simultaneously, ROA and CR significantly affect capital structure, with an R² value of 14.5%, while the remaining variation is explained by other factors not included in this study. These findings support the trade-off theory, which posits that firms balance the benefits of debt with potential financial risks to achieve an optimal structure. The study highlights the critical role of liquidity management in capital structure decisions and recommends its prioritization for firms in the real estate industry.